Moral Hazard, Aristotle's Virtue Ethics and Accounting Education in the Preparation of Corporate Financial Reports: Systematic Literature Review. - Parwati, Tri Ayu; Wahyudi, Rahmat; Suryadi, Dodi; Viona, Resyelly (UPI YPTK Journal of Business and Economics, 2025)
The main objective of this study is to explore the relationship between moral hazard, virtue ethics and accounting education in the context of financial statement preparation practices. The literature search process was conducted using seven keyword combinations: Virtue Ethics AND Accounting Education, Virtue Ethics AND Financial Reporting, Moral Hazard AND Accounting Ethics, Accounting Education AND Ethics Integration, Financial Reporting AND Virtue Ethics, Ethical Decision Making AND Accounting Profession, Accounting Education AND Integrity in Financial Reporting. From this search, 1 article was found in Web of Science journals, 2 articles in Elsevier journals, 3 articles in Springer journals, 1 article in Willey-Blackweell journals, 2 articles in Taylor & Francis journals, 1 article in SAGE Publications journals, 4 articles in Emerald journals, 2 articles in ProQuest journals, 1 article in Ebsco journals and 2 articles in MDPI journals. The results of the literature review indicate that moral hazard in the accounting world can be minimized with an approach based on Aristotle's virtue ethics, which encourages accountants to develop personal virtues such as honesty, courage, and wisdom. Accounting education that focuses on these ethical values is expected to create accountants who are not only technically competent, but also have high moral awareness, so that the financial statements produced are more trustworthy and reflect the true financial condition of the company.